Potential therapeutic effect of NK1R antagonist in diabetic non-healing wound and depression - Li, Mingyu; Ma, Hao; Zhang, Shunuo; Peng, Yuan; Ding, Liang; Zhang, Yixin; Min, Peiru (Frontiers in Endocrinology, 2023)
Diabetes is a global disease with huge impacts on patients due to its complications, among which non-healing wounds and depression are common and challenging. The neurokinin 1 receptor (NK1R) inhibitor, aprepitant has been broadly applied for an antidepressant effect in depressive patients. Recent literature has indicated a therapeutic effect of downregulation in NK1R to diabetes-related fracture, cardiomyopathy, gastroparesis, and ocular surface disorders. In this study, differential expression genes in diabetes and depression were analyzed based on several RNA sequencing datasets from the GEO database to confirm NK1R in the overlapping set. Interaction network and gene set enrichment analysis were subsequently conducted. As a result, NK1R-related genes took part in angiogenesis, epithelial-mesenchymal transition (EMT), collagen deposition, and inflammation in diabetes and depression. In vivo, the downregulation of NK1R was proved to promote vascular proliferation and enhance diabetic wound healing, which provides a potential therapeutic target for the management of diabetic non-healing wounds and depression.